Kompetensi Komunikasi Guru SLB Mengenai Pendidikan Seks Usia Dini pada Anak Berkebutuhan Khusus Tunarungu - Monica Hayunindya Patria Paramesthi; Turnomo Rahardjo (Interaksi Online, 2021)
Teachers are the intermediary for deaf children at SLB Negeri Ungaran to get sex education. Therefore, teacher’s communication competence regarding sex education for deaf children at SLB Negeri Ungaran becomes necessary. So, sex education can be conveyed and understood by deaf children properly. This study aimed to describe teacher’s communication competence regarding sex education for deaf children in SLB Negeri Ungaran. This study using qualitative research methods with an interpretive paradigm and a phenomenological approach. The research subjects are four teachers of SLB Negeri Ungaran who taught sex education. The theories used are Communication Competence Theory, Compliance Gaining Theory, and Effective Communication Theory. The result indicates that all teachers have the motivation in providing sex education for deaf children. The motivation arises because the teacher was concerned about their students and their bad experience in the past regarding sexual harassment and pregnancy before marriage that happened to deaf children. Teachers also have the knowledge of sex education for deaf children. However, the knowledge that one and other teachers have is not the same, because it’s not in the curriculum. The teacher’s knowledge comes from their references and personal experience in dealing directly with cases of sexual harassment and pregnancy before marriage. Not all teachers have skills in providing sex education for deaf children. All teachers have compliance gaining strategies. Teacher’s compliance gaining strategies are focused on verbal using sign language than nonverbal strategies. The approach taken in this strategy is a kind and subtle approach. There are several obstacles between teachers and their students in providing sex education, namely, different-sex-education materials, taboo assumptions about sex education, gadgets, and the internet. Not all teachers can effectively communicate to their students in providing sex education, because not all their students can understand. It happens because of the lack of skills that teachers have in providing sex education for deaf children likewise some obstacles between teachers and their students.